How to evaluate materials

JP7633066B2Active Publication Date: 2025-02-19TDK CORP
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2021058807
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-03-30
Publication Date
2025-02-19
Estimated Expiration
2041-03-30

Smart Images

  • Figure 0007633066000003
    Figure 0007633066000003
  • Figure 0007633066000004
    Figure 0007633066000004
  • Figure 0007633066000005
    Figure 0007633066000005
Patent Text Reader

Abstract

To provide a material evaluation method which allows for objectively identifying microstructures of a material.SOLUTION: A material evaluation method is provided, comprising acquiring an image of a cross-section of a material, dividing the acquired image into multiple sections, measuring brightness of a plurality of pixels in each section, obtaining a brightens histogram of each section from brightens of each pixel, and identifying a microstructure of each section from the brightness histogram of each section.SELECTED DRAWING: Figure 9
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for evaluating a material. [Background technology]

[0002] Patent Document 1 describes an invention related to a method for evaluating the metal structure of a rare earth-containing alloy. Specifically, it describes a method of drawing a straight line in a specific direction in a microscopic image of a cross section of a rare earth-containing alloy, and distinguishing the main phase from the R-rich phase based on the brightness of the main phase and the brightness of the R-rich phase that intersect with the straight line. In the evaluation method of Patent Document 1, the R-rich phase interval is calculated by dividing the number of times the brightness of the main phase changes to the brightness of the R-rich phase by the length of the straight line. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2008-058323 A Summary of the Invention [Problem to be solved by the invention]

[0004] An object of the present invention is to provide an evaluation method capable of objectively identifying the microstructure of a material. [Means for solving the problem]

[0005] In order to achieve the above object, the material evaluation method according to the present invention comprises the steps of: obtaining an image of a cross-section of the material; Dividing the obtained image into a number of sections; measuring the luminance of a plurality of pixels included in each partition; obtaining a luminance histogram for each section from the luminance of each pixel; and identifying the fine structure of each section from the luminance histogram of each section.

[0006] The material may be an alloy.

[0007] The alloy may be an RTB permanent magnet alloy, where R is a rare earth element, T is a transition metal element, and B is boron.

[0008] The type of the fine structure of each section may be identified from the peak position and peak standard deviation in the brightness histogram of each section.

[0009] The method may further include a step of calculating the total area ratio of sections having the specific microstructure.

[0010] When the luminance histogram is created in 256 gradations with the minimum luminance being 0 and the maximum luminance being 255, the total area ratio of the sections in which the peak position is 130 to 200 and the peak standard deviation is 20 to 40 may be calculated.

[0011] embedding two or more image preparation plates in a substrate to contain them within the same field of view of an electron microscope; creating an unadjusted luminance histogram for the field of view; adjusting the positions of the luminance peaks originating from each thin plate in the unadjusted luminance histogram to a predetermined position and adjusting the difference between the positions of the luminance peaks originating from each thin plate to a predetermined size; An image of a cross section of the material may be obtained using an electron microscope adjusted using a method for adjusting an electron microscope comprising: [Brief description of the drawings]

[0012] [Figure 1] This is a backscattered electron image of normal tissue. [Diagram 2] This is a backscattered electron image of chill crystal structure. [Diagram 3] This is a backscattered electron image of a structure containing fine dots of R-rich phase. [Figure 4] This is a backscattered electron image of a structure containing fine dots of R-rich phase. [Diagram 5] This is a backscattered electron image of a structure containing dot-like R-rich phases. [Figure 6]This is a backscattered electron image of a structure containing fine linear R-rich phases. [Figure 7] This is a backscattered electron image of a structure containing fine linear R-rich phases. [Figure 8] This is a backscattered electron image of a structure containing large dot-like R-rich phases. [Figure 9] This is a backscattered electron image of an evaluation sample divided into sections. [Figure 10] 10 is a luminance histogram for one section of FIG. [Figure 11] 1 is a graph showing differences in peak position and σ of brightness histograms depending on tissue. [Figure 12] FIG. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0013] Hereinafter, the present invention will be described based on the embodiments shown in the drawings.

[0014] The material evaluation method according to the present embodiment includes the steps of: obtaining an image of a cross-section of the material; Dividing the obtained image into a plurality of regions; measuring the luminance of a plurality of pixels included in each region; obtaining a luminance histogram for each region from the luminance of each pixel; The method further comprises a step of identifying the fine structure of each region from the shape of the luminance histogram of each region.

[0015] According to the material evaluation method of the present embodiment, for a material having multiple types of texture, it is possible to identify which section of the material has which type of texture in an objective manner that does not depend on the experience of each individual. This method is simple in that it requires a short time to identify the texture and is easy to automate. Furthermore, this method is accurate in that it is identified in an objective manner, so there is no error due to differences in the person making the measurement.

[0016] Hereinafter, the case of an alloy which is one kind of material, particularly an alloy for an R-T-B permanent magnet to which the evaluation method according to the present embodiment can be preferably applied, will be described.

[0017] <Microstructure of alloy for R-T-B permanent magnet> The alloy for an R-T-B permanent magnet to which the evaluation method according to the present embodiment is applied is an alloy for an R-T-B permanent magnet having R, T, and B, where R is a rare earth element, T is a transition metal element, and B is boron.

[0018] Generally, an alloy for an R-T-B permanent magnet contains a main phase which is columnar crystals having an R2T 14 B-type crystal structure, and an R-rich phase having a higher R content than the main phase.

[0019] In the cross-section of the alloy for an R-T-B permanent magnet, as shown in the backscattered electron image of FIG. 1, a clear difference can be confirmed between the main phase 11 and the R-rich phase 13, and a structure 7 (hereinafter, usually referred to as the normal structure 7) in which most of the shapes of the R-rich phases 13 are linear occupies the majority. Most of the main phases 11 contained in the normal structure 7 are columnar crystals. In the normal structure 7, the average interval between the R-rich phases (hereinafter, referred to as linear R-rich phases) having a linear shape is 2 μm or more. Also, the normal structure 7 is a structure in which primary dendrites extend in the direction of solidification of the alloy, in other words, in the thickness direction of the alloy.

[0020] In addition to the normal structure 7, the alloy for an R-T-B permanent magnet includes a structure containing a main phase that is not a columnar crystal. The main phase that is not a columnar crystal is called a non-columnar crystal, and the structure containing a non-columnar crystal is called a non-columnar crystal structure. Also, the non-columnar crystal structure is not necessarily a structure in which primary dendrites extend in the direction of solidification of the alloy.

[0021] The non-columnar crystal structure contained in the alloy for an R-T-B permanent magnet is classified into six types when distinguishing between the structure 1a and the structure 1b described later. Hereinafter, the six types of non-columnar crystal structures will be described with reference to the drawings (backscattered electron images).

[0022] Figure 2 includes chilled crystal structure 1, which includes structures 1a and 1b. Structure 1a is more different from normal structure 7 than structure 1b. In structure 1a, no clear difference is seen between the main phase and the R-rich phase. The brightness of structure 1a in a backscattered electron image is intermediate between that of the main phase and the R-rich phase. Furthermore, the variation in shading in a backscattered electron image of structure 1a is smooth.

[0023] Structure 1b is closer to normal structure 7 than structure 1a. However, structure 1b shows no clear difference between the main phase and the R-rich phase. The brightness of structure 1b in the backscattered electron image is intermediate between that of the main phase and the R-rich phase. Furthermore, the variation in shading in the backscattered electron image of structure 1b is smooth. Also, unlike structure 1a, structure 1b partially contains linear R-rich phases.

[0024] In the following description, when simply referring to chill crystal structures, no distinction is made between structure 1a and structure 1b.

[0025] 3 and 4 include a fine dot-like R-rich phase-containing structure 3 (hereinafter, sometimes referred to as structure 3). Different alloy pieces are observed in Figs. 3 and 4. In structure 3, a clear difference is observed between the main phase and the R-rich phase. However, compared to the normal structure 7 shown in Fig. 1, in structure 3, the R-rich phase aggregates in dots and is excessively dense. Furthermore, compared to the dot-like R-rich phase-containing structure 4 described below, the dot-like R-rich phase is finer.

[0026] For example, the dot-like R-rich phases contained in the structure 3 may have a size of 0.3 to 1.5 μm in terms of circle equivalent diameter, and the number of dot-like R-rich phases per unit area may be 0.25 pieces / μm 2 It may be more than that.

[0027] Furthermore, structure 3 can be cut into sections where the circle equivalent diameter and density of the dot-like R-rich phase are subtly different locally. The actual cut state is shown by dotted lines in Figure 4. The cut polygonal regions may have a long axis of 10 μm or more and 120 μm or less, and a short axis of 5 μm or more and 80 μm or less. The long axis refers to the longest distance between two parallel lines that contact the polygon from both sides, and the short axis refers to the shortest distance between two parallel lines that contact the polygon from both sides.

[0028] FIG. 5 includes a dot-like R-rich phase-containing structure 4 (hereinafter, sometimes referred to as structure 4). Structure 4 has a larger dot-like R-rich phase itself than structure 3. Furthermore, in the portion where the dot-like R-rich phase aggregates, a phase darker than the main phase exists.

[0029] 6 and 7 include a microstructure 5 containing fine linear R-rich phases (hereinafter, sometimes referred to as structure 5). Different alloy pieces are observed in Figs. 6 and 7. In structure 5, a clear difference is observed between the main phase and the R-rich phase. However, in structure 5, the linear R-rich phases are thinner and excessively denser than in the normal structure 7 shown in Fig. 1.

[0030] For example, the linear R-rich phases contained in the structure 5 may have a length of 4 to 125 μm, a width of 0.3 to 10 μm, and an interval between the linear R-rich phases of 1.0 to 1.8 μm.

[0031] Furthermore, the structure 5 can be cut into portions where the length, width, and density of the linear R-rich phase are subtly different locally. The actual cut state is shown by dotted lines in Fig. 7. The cut polygonal regions may have a major axis of 30 μm or more and 200 μm or less and a minor axis of 5 μm or more and 150 μm or less.

[0032] FIG. 8 includes a large dot-like R-rich phase-containing structure 6 (hereinafter, sometimes referred to as structure 6). In structure 6, the R-rich phase is aggregated to a large extent. The brightness of the main phase around the aggregated R-rich phase is slightly higher. Also, linear R-rich phases may be sandwiched between the large aggregated R-rich phases.

[0033] In the evaluation method according to this embodiment, the area ratio of the non-columnar crystal structure in the cross section of an RTB permanent magnet alloy can be evaluated by a method other than visual inspection, that is, a method not dependent on human hands.

[0034] <Method for evaluating the area ratio of non-columnar crystal structure> In the evaluation method according to the present embodiment, brightness analysis of a backscattered electron image is used to evaluate the microstructure of a material. Below, a method of brightness analysis will be described in particular for evaluating the area ratio of the non-columnar crystal structure in the cross section of an RTB permanent magnet alloy, but various conditions may be appropriately changed depending on the type of material.

[0035] First, in preparation for the brightness analysis, the brightness and contrast of the electron microscope are adjusted.

[0036] First, an alloy plate for an RTB permanent magnet is prepared as a material for a standard sample. The alloy plate for an RTB permanent magnet may be used as it is, or a heat-treated plate obtained by subjecting the alloy plate for an RTB permanent magnet to heat treatment may be used. By carrying out the heat treatment, the process of bringing only the main phase 11 into the field of view of the electron microscope becomes easier. As a result, it becomes easier to adjust the brightness and contrast of the electron microscope. When carrying out the heat treatment, there is no particular limit to the heat treatment time and temperature. For example, the heat treatment is carried out at 800 to 1000°C for 30 to 120 minutes.

[0037] Next, a plurality of metal thin plates for adjusting images, that is, metal thin plates for adjusting brightness and contrast, are prepared. For example, Ni thin plate, Cu thin plate, and Zn thin plate are prepared. Then, the alloy plate for RTB permanent magnet, Ni thin plate, Cu thin plate, and Zn thin plate are embedded in a substrate. For example, an embedding resin for electron microscope observation is used as the substrate. At this time, the plates are arranged so that the cross sections parallel to the thickness direction are aligned, and a standard sample is prepared. At this time, there is no particular restriction on the type of thin plate other than the alloy plate for RTB permanent magnet, and at least two types of thin plate are sufficient. The luminance peak position of each metal and the difference between the luminance peak positions of each metal, which will be described later, may be appropriately set according to the type of thin plate. In the following description, a case where Ni thin plate, Cu thin plate, and Zn thin plate are used will be described.

[0038] Next, the cross section of the standard sample is mirror-polished and gold is evaporated. By mirror-polishing the cross section and evaporation of gold, the brightness and contrast can be suitably adjusted.

[0039] Next, the standard sample is set in the electron microscope. The imaging mode is backscattered electron imaging. There is no particular limit to the number of pixels, which varies depending on the material being observed. For example, 1280 x 960 pixels. There is no particular limit to the magnification, but the magnification should be such that the Ni thin plate, Cu thin plate, and Zn thin plate are in the same field of view.

[0040] Next, the field of view is shifted so that the Ni thin plate, the Cu thin plate, and the Zn thin plate are included in that order in the same field of view.

[0041] Next, a pre-adjustment luminance histogram is created for the field of view with 256 gradations, with the minimum luminance being 0 and the maximum luminance being 255. After that, the position of the luminance peak derived from each metal thin plate is adjusted to a predetermined position according to the type of material and the type of metal thin plate. Then, the difference between the positions of the luminance peak derived from each metal thin plate is controlled to a predetermined magnitude. In this embodiment, the brightness is adjusted so that the position of the luminance peak derived from the Cu thin plate is about 150 (145 to 155). Furthermore, the contrast is adjusted so that the difference between the position of the luminance peak derived from the Ni thin plate and the position of the luminance peak derived from the Cu thin plate is about 55 (45 to 65), and the difference between the position of the luminance peak derived from the Cu thin plate and the position of the luminance peak derived from the Zn thin plate is about 45 (35 to 55). When adjusting the contrast, the brightness is adjusted as necessary in an auxiliary manner in order to maintain the state in which the position of the luminance peak derived from the Cu thin plate is about 150.

[0042] Next, while maintaining the contrast, the field of view of the electron microscope is moved to a position where the RTB permanent magnet alloy plate is placed. The brightness is appropriately controlled depending on the type of material and the type of thin metal plate. In this embodiment, the magnification is increased so that the white phase (R-rich phase 13) does not appear in the field of view and only the main phase 11 appears in the field of view. The magnification may be up to about 10,000 times. Furthermore, the brightness is adjusted so that the peak position of the brightness histogram is about 110 (105 to 115). Finally, the standard sample is collected from the electron microscope.

[0043] Next, the method of luminance analysis will be described.

[0044] First, prepare a material to be subjected to brightness analysis. The following describes the case where the material is an alloy for an RTB permanent magnet. Next, process the alloy for an RTB permanent magnet so that its cross section can be observed, and prepare an evaluation sample. Multiple evaluation samples may be prepared and the results obtained may be averaged.

[0045] Next, set the imaging mode to backscattered electron image and set the observation range. Measurement conditions vary depending on the type of material and the microstructure to be evaluated, but when evaluating the above microstructure of an RTB permanent magnet alloy, set the observation range to a magnification of 350x and a pixel count of 1280 x 960 pixels. Note that with the above magnification and pixel count, the observation range is 360 μm x 270 μm.

[0046] Next, the portion of the evaluation sample included in the above observation range is divided into sections at regular intervals. There is no particular limit to the size of each section, and it varies depending on the type of material and the microstructure to be evaluated. When evaluating the above microstructure of an RTB permanent magnet alloy, it is preferable to set the size to 40 pixels or more and 60 pixels or less, and 50 pixels is particularly preferable. Figure 9 shows an image in which the cross section of an actual evaluation sample was observed and divided into sections with a size of 50 pixels. A cross section parallel to the thickness direction of the RTB permanent magnet alloy was observed, and the size of the image in Figure 9 is 1280 pixels (= 360 μm) horizontally and 960 pixels (= 270 μm) vertically for the entire Figure 9.

[0047] Next, a luminance histogram is created for each section. For example, the luminance histogram for the seventh section from the top and the third section from the left in Figure 9 is shown in Figure 10. The fine structure of each section is then identified from the shape of the luminance histogram.

[0048] When evaluating the above-mentioned microstructure of an RTB permanent magnet alloy, whether each section has a normal structure or a non-columnar structure is identified from the shape of the brightness histogram. Specifically, the peak position and standard deviation (σ) of the brightness histogram are obtained for each section, and the type is identified from the obtained peak position and σ. A specific example of an RTB permanent magnet alloy is described below.

[0049] The present inventors observed the cross sections of many RTB permanent magnet alloys. Then, the backscattered electron images of the cross sections obtained by the above method were visually observed and classified into normal structures and six types of non-columnar crystal structures. Then, the positions of the peaks and the tendency of σ in the brightness histograms of each structure were observed.

[0050] As a result, in most of the sections with non-columnar crystal structure, the brightness histograms had peak positions between 130 and 200, and σ between 20 and 40. In contrast, in most of the sections with normal structure 7, the brightness histograms had σ above 40.

[0051] Fig. 11 shows the average peak positions and average σ of the sections corresponding to the normal structure and the sections corresponding to six types of non-columnar crystal structures. Most of the sections corresponding to Structure 1a, Structure 1b, and Structure 3 to Structure 6 had peak positions between 130 and 200, and σ between 20 and 40.

[0052] From the above, it can be considered that a section has a non-columnar crystal structure when the peak position of the brightness histogram is between 130 and 200 and σ is between 20 and 40. The ratio of the number of sections whose peak positions and σ of the brightness histogram are within the above ranges to all sections can be considered to be the area ratio of the non-columnar crystal structure.

[0053] It was also found that RTB permanent magnets produced using alloys for RTB permanent magnets in which the area ratio of the non-columnar crystal structure specified by the above method is 1.0% or more and 30.0% or less have good magnetic properties. In particular, it was found that when the area ratio is 1.0% or more, HcJ at high temperatures tends to be high. It was also found that when the area ratio is 30% or less, Hk / HcJ at room temperature tends to be high. It was found that the area ratio of the non-columnar crystal structure is preferably 4.0% or more and 30.0% or less.

[0054] Furthermore, a section where the position of the peak of the luminance histogram is 130 or more and 200 or less and σ is 30 or more and 40 or less can be regarded as a structure other than the chill crystal structure in the non-columnar crystal structure. And it has been found that the area ratio of the structure other than the chill crystal structure in the non-columnar crystal structure may be 50% or more, preferably 85% or more and 95% or less, and more preferably 87% or more and 91% or less.

[0055] Regarding each section for creating the luminance histogram, when the size of one section is too large, it often includes two or more different structures within the same section. When the size of one section is too small, the number of pixels included in each section decreases, so the accuracy of the luminance histogram created for each section decreases. As a result, the peak position and σ of the luminance histogram become unclear. That is, there is an appropriate range for the size of one section according to the type of material, etc.

[0056] <Composition of the R-T-B system permanent magnet alloy> The composition of the R-T-B system permanent magnet alloy is not particularly limited. R represents at least one of rare earth elements. Rare earth elements refer to Sc, Y, and lanthanoid elements belonging to Group 3 of the long-period type periodic table. Lanthanoid elements include, for example, La, Ce, Pr, Nd, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, Lu, etc. Rare earth elements are classified into light rare earth elements and heavy rare earth elements. Heavy rare earth elements refer to Gd, Tb, Dy, Ho, Er, Tm, Yb, Lu, and light rare earth elements are rare earth elements other than heavy rare earth elements. In the present embodiment, from the viewpoint of suitably controlling the manufacturing cost and magnetic properties, Nd and / or Pr may be included as R. Also, from the viewpoint of particularly improving HcJ, both light rare earth elements and heavy rare earth elements may be included. There is no particular limitation on the content of heavy rare earth elements, and they may not be included. The content of heavy rare earth elements is, for example, 5 mass% or less (including 0 mass%).

[0057] The content of R may be 29.0% by mass or more and 33.5% by mass or less. If the content of R is small, the HcJ of the resulting RTB permanent magnet tends to decrease. If the content of R is large, the Br tends to decrease.

[0058] The content of B may be 0.70% by mass or more, or 0.80% by mass or more. The upper limit of the content of B may be less than 1.0% by mass, less than 0.96% by mass, or 0.90% by mass or less. When the content of B is smaller than the stoichiometric ratio, specifically, when it is less than 1.0% by mass, the area ratio of the non-columnar crystal structure is easily set to 1.0 to 30.0%. When the content of B is small, Hk / HcJ is easily decreased. Furthermore, abnormal grain growth is easily generated when sintering at high temperatures. Furthermore, when sintering at low temperatures, Hk / HcJ is difficult to increase. When the content of B is large, abnormal grain growth is easily generated. And Br is easily decreased.

[0059] T is a transition metal element. It may be Fe alone or Fe and Co. The Co content may be 0% by mass or more and 2.0% by mass or less. The smaller the Co content, the more likely abnormal grain growth occurs when sintering at high temperatures. Also, when sintering at low temperatures, it is difficult to increase Hk / HcJ. When the Co content is large, Br and HcJ decrease. Also, RTB permanent magnet alloys tend to be expensive.

[0060] The RTB permanent magnet alloy may contain M. M is one or more selected from Cu, Ga, Zr, and Al. There is no particular limit to the total content of M. It may be 0.1% by mass or more and 2.0% by mass or less.

[0061] There is no particular limit to the Cu content. For example, it may be 0.05% by mass or more and 0.50% by mass or less. By including 0.05% by mass or more of Cu, abnormal grain growth is less likely to occur when sintering at high temperatures. In addition, even when sintering at low temperatures, Hk / HcJ tends to be sufficiently high. By including 0.50% by mass or less of Cu, Br tends to be improved.

[0062] There is no particular limit to the Ga content. For example, it may be 0% by mass or more and 1.0% by mass or less. By including Ga, abnormal grain growth is less likely to occur when sintering at high temperatures. Furthermore, even when sintering at low temperatures, Hk / HcJ tends to be sufficiently high. Furthermore, HcJ tends to be improved. By including 1.0% by mass or less of Ga, Br tends to be improved.

[0063] There is no particular limit to the Al content. For example, it may be 0.05% by mass or more and 1.00% by mass or less. By including 0.05% by mass or more of Al, HcJ is likely to be improved. Furthermore, even when sintering at high temperatures, abnormal grain growth is unlikely to occur. Furthermore, even when sintering at low temperatures, Hk / HcJ tends to be sufficiently high. By including 1.00% by mass or less of Al, Br is likely to be improved.

[0064] There is no particular limit to the Zr content. For example, it may be 0.05% by mass or more and 1.00% by mass or less. By including 0.05% by mass or more of Zr, Hk / HcJ tends to be sufficiently high even when sintered at a low temperature. In addition, abnormal grain growth is less likely to occur even when sintered at a high temperature. By including 1.00% by mass or less of Zr, Br tends to be improved.

[0065] The Fe content is the substantial balance in the components of the RTB permanent magnet alloy. The Fe content being the substantial balance refers to the case where the total content of elements other than R, Fe, Co, B, and M is 1.0 mass% or less.

[0066] The RTB system permanent magnets produced using the above alloys for RTB system permanent magnets are processed into any shape for use. The shape of the RTB system permanent magnet is not particularly limited, and can be any shape, such as a rectangular parallelepiped, hexahedron, flat plate, columnar such as a square column, or a cylindrical shape with a C-shaped cross section.

[0067] In addition, the R-T-B-based permanent magnets include both magnet products obtained by processing and magnetizing the magnets and magnet products that have not been magnetized.

[0068] <Method for manufacturing an alloy for an R-T-B-based permanent magnet> As an example of a method for manufacturing an alloy for an R-T-B-based permanent magnet, a method of manufacturing by the strip casting method using the casting apparatus shown in FIG. 12 will be described.

[0069] The casting apparatus shown in FIG. 12 has a cooling roll 21 and a tundish 23. Although not shown in FIG. 12, the casting apparatus may have components well known as components of the casting apparatus, such as a refractory crucible and a collection container. There is no particular limitation on the type of refractory crucible. For example, an alumina crucible, a mullite crucible, a zirconia crucible, etc. can be mentioned. There is no particular limitation on the material of the cooling roll 21. For example, copper, a copper alloy, a material obtained by plating or spraying on the surface of copper, a material obtained by plating or spraying on the surface of a copper alloy, etc. can be mentioned.

[0070] First, raw materials are weighed and mixed so as to have the alloy composition of the target alloy for an R-T-B-based permanent magnet to obtain a raw material mixture.

[0071] Next, the obtained raw material mixture is loaded into a refractory crucible, and the loaded raw material mixture is melted to obtain an alloy melt. There is no particular limitation on the method of melting the raw material mixture. For example, a method of heating a refractory crucible loaded with the raw material mixture by installing it in a high-frequency vacuum induction furnace can be mentioned.

[0072] Then, the obtained alloy melt is cast by the strip casting method using the casting apparatus shown in FIG. 12 to obtain a cast alloy ribbon (alloy for an R-T-B-based permanent magnet). Specifically, the alloy melt 25 is supplied to the internally water-cooled cooling roll 21 via the tundish 23. The alloy melt 25 supplied onto the cooling roll 21 is cooled and detached from the cooling roll 21 on the opposite side of the tundish 23, and is recovered as a cast alloy ribbon.

[0073] Of the cast alloy ribbon, the surface in contact with the chill roll 21 is the roll surface, and the surface opposite to the roll surface is the free surface. The roll surface is cooled more rapidly by the chill roll 21 than the free surface. Here, a non-columnar crystal structure is more likely to form when the cooling rate is faster than that of a normal crystal structure. Among the non-columnar crystal structures, a chill crystal structure is more likely to form when the cooling rate is particularly fast. Therefore, a chill crystal structure and a non-columnar crystal structure are more likely to form on the roll surface than on the free surface. Note that the roll surface is on the left side in all of Figures 1 to 9.

[0074] The area ratio of the non-columnar crystal structure (chill crystal structure) varies mainly depending on the temperature (casting temperature) of the molten alloy 25, the composition of the molten alloy 25, the roll surface roughness Rz of the chill roll 21, the shape of the unevenness that affects the roll surface roughness Rz, the molten alloy head pressure 27, the roll circumferential speed of the chill roll 21, and the supply speed of the molten alloy 25 to the chill roll 21 (the supply speed per unit contact width between the molten alloy 25 and the chill roll 21). The temperature of the molten alloy 25 is, for example, 1300 to 1600°C. The roll surface roughness Rz of the chill roll 21 is, for example, 10 to 50 μm. The roll circumferential speed of the chill roll 21 is, for example, 0.5 to 2.5 m / s. The supply speed of the molten alloy 25 to the chill roll 21 is, for example, 0.5 to 2.5 kg / (min cm).

[0075] The molten metal head pressure 27 will be described below. The molten metal head pressure 27 refers to the depth of the molten alloy 25 in contact with the chill roll 21. The higher the molten metal head pressure 27, the stronger the pressure with which the molten alloy 25 is pressed against the chill roll 21 by its own weight. Therefore, the higher the molten metal head pressure 27, the stronger the adhesion between the molten alloy 25 and the chill roll 21 becomes, and the higher the heat transfer coefficient from the molten alloy 25 to the chill roll 21 becomes. At the same time, the length of the molten alloy 25 in contact with the chill roll 21 also changes. Therefore, if other conditions are the same, the higher the molten metal head pressure 27, the thicker the cast alloy ribbon will be. In practice, the molten metal head pressure 27 is appropriately selected in accordance with other casting conditions.

[0076] As described above, the faster the cooling rate, the easier it is to form a non-columnar crystal structure (chill crystal structure). Therefore, the larger the melt head pressure 27, the greater the tendency for the area ratio of the non-columnar crystal structure (chill crystal structure) to be larger.

[0077] As a method for increasing the melt head pressure 27, a method of increasing the amount of alloy melt 25 in the tundish 23 can be mentioned. As a method for increasing the amount of alloy melt 25 in the tundish 23, a method of increasing the supply rate of the alloy melt 25 to the tundish 23 can be mentioned. If the supply rate of the alloy melt 25 to the tundish 23 increases, the cast alloy ribbon becomes thicker. As a method for increasing the melt head pressure 27 without changing the thickness of the cast alloy ribbon, a method of increasing the peripheral speed of the cooling roll 21 can be mentioned.

[0078] That is, when producing a cast alloy ribbon of the same thickness, when the supply rate of the alloy melt 25 is fast and the peripheral speed of the cooling roll 21 is fast, the melt head pressure 27 becomes large, and when the supply rate of the alloy melt 25 is slow and the peripheral speed of the cooling roll 21 is slow, the melt head pressure 27 becomes small.

[0079] There is no particular limitation on the method for producing an R-T-B-based permanent magnet using the alloy for an R-T-B-based permanent magnet produced by the above method.

[0080] The present invention is not limited to the above-described embodiments, and various modifications can be made within the scope of the present invention. By changing various measurement conditions, it can also be used to specify the fine structure of alloys other than the alloy for an R-T-B-based permanent magnet and the fine structure of materials other than alloys.

[0081] <Method for manufacturing an R-T-B-based permanent magnet> There is no particular limitation on the method for producing an R-T-B-based permanent magnet using the alloy for an R-T-B-based permanent magnet produced by the above method. For example, a method having the following steps can be mentioned. (a) A pulverizing step of pulverizing the alloy for an R-T-B-based permanent magnet (b) A forming step of forming the obtained alloy powder (c) Sintering process to obtain RTB permanent magnets by sintering the green body (d) Aging treatment process for aging RTB permanent magnets (e) Cooling process for cooling RTB permanent magnets (f) Processing process for RTB permanent magnets (g) Grain boundary diffusion process in which heavy rare earth elements are diffused into the grain boundaries of RTB permanent magnets (h) Surface treatment process for RTB permanent magnets

[0082] [Crushing process] The RTB permanent magnet alloy is pulverized (pulverization process). The pulverization process includes a coarse pulverization process in which the alloy is pulverized to a particle size of several hundred μm to several mm, and a fine pulverization process in which the alloy is pulverized to a particle size of about several μm.

[0083] (Coarse grinding process) The RTB permanent magnet alloy is coarsely pulverized until the particle size is about several hundred μm to several mm (coarse pulverization step). This produces a coarsely pulverized powder of the RTB permanent magnet alloy. The coarse pulverization can be performed, for example, by absorbing hydrogen into the RTB permanent magnet alloy, then releasing hydrogen based on the difference in the amount of hydrogen absorbed between different phases, and dehydrogenating the alloy to cause self-destructive pulverization (hydrogen absorption pulverization).

[0084] The coarse pulverization step may be performed in an inert gas atmosphere using a coarse pulverizer such as a stamp mill, a jaw crusher, or a Braun mill, other than the hydrogen absorption pulverization method described above.

[0085] The oxygen concentration is adjusted by controlling the atmosphere in each manufacturing process. From the viewpoint of obtaining high magnetic properties, the oxygen content of the finally obtained RTB permanent magnet may be reduced. To achieve this, the oxygen concentration in each process from the grinding process to the sintering process described below may be set to 100 ppm or less.

[0086] (Fine grinding process) After the RTB permanent magnet alloy is coarsely pulverized, the obtained coarsely pulverized powder of the RTB permanent magnet alloy is finely pulverized until the average particle size is about several μm (fine pulverization step). This produces finely pulverized powder of the RTB permanent magnet alloy. By further finely pulverizing the coarsely pulverized powder, finely pulverized powder having particles of, for example, 1 μm to 10 μm, or 3 μm to 5 μm can be obtained.

[0087] Fine pulverization is performed by further pulverizing the coarsely pulverized powder using a fine pulverizer such as a jet mill, ball mill, vibration mill, wet attritor, etc., while appropriately adjusting conditions such as pulverization time. A jet mill is a method in which a high-pressure inert gas (e.g., N2 gas) is released from a narrow nozzle to generate a high-speed gas flow, and this high-speed gas flow accelerates the coarsely pulverized powder of the raw alloy, causing collisions between the coarsely pulverized powder of the raw alloy and with a target or the wall of a container, thereby pulverizing the powder.

[0088] When the coarsely pulverized powder of the raw alloy is pulverized, a pulverization aid such as zinc stearate, urea, stearic acid amide, or oleic acid amide can be added to obtain a finely pulverized powder with a high degree of orientation during compaction.

[0089] [Molding process] The pulverized powder is molded into the desired shape (molding process). In the molding process, the pulverized powder is filled into a die surrounded by an electromagnet and pressurized to mold the pulverized powder into any shape. This is done while a magnetic field is applied, which creates a specific orientation in the pulverized powder, and the powder is molded in the magnetic field with the crystal axes oriented. This produces a molded body. The resulting molded body is oriented in a specific direction, resulting in an RTB permanent magnet with stronger magnetic anisotropy.

[0090] The pressure during molding may be 30 MPa to 300 MPa. The magnetic field applied may be 950 kA / m to 1600 kA / m. The magnetic field applied is not limited to a static magnetic field, and may be a pulsed magnetic field. A static magnetic field and a pulsed magnetic field may also be used in combination.

[0091] As a molding method, in addition to the dry molding in which the finely pulverized powder is molded as is as described above, wet molding in which a slurry in which the finely pulverized powder is dispersed in a solvent such as oil can also be applied.

[0092] The shape of the green body obtained by compacting the finely pulverized powder is not particularly limited, and can be any shape depending on the desired shape of the RTB permanent magnet, such as a rectangular parallelepiped, flat plate, column, ring, etc.

[0093] [Sintering process] The green body obtained by molding in a magnetic field and forming into the desired shape is sintered in a vacuum or inert gas atmosphere to obtain an RTB permanent magnet (sintering process). The sintering temperature needs to be adjusted depending on various conditions such as the composition, the pulverization method, the particle size and particle size distribution, etc. The green body is sintered, for example, by heating in a vacuum or in the presence of an inert gas at 1000°C to 1200°C for 1 hour to 48 hours. This causes liquid phase sintering of the finely pulverized powder, and an RTB permanent magnet (sintered body of RTB magnet) with an increased volume ratio of main phase particles is obtained. After sintering the green body to obtain the sintered body, the sintered body may be rapidly cooled from the viewpoint of improving production efficiency.

[0094] [Aging treatment process] After sintering the compact, the RTB permanent magnet is subjected to an ageing treatment (aging treatment step). After sintering, the RTB permanent magnet is subjected to an ageing treatment by, for example, holding the obtained RTB permanent magnet at a temperature lower than that at the time of sintering. The aging treatment may be, for example, a two-stage heating at a temperature of 700°C or higher and 1000°C or lower for 10 minutes to 6 hours, and then a one-stage heating at a temperature of 500°C to 700°C for 10 minutes to 6 hours, or a one-stage heating at a temperature of about 600°C for 10 minutes to 6 hours, and the treatment conditions are appropriately adjusted depending on the number of times the aging treatment is performed. Such an aging treatment can improve the magnetic properties of the RTB permanent magnet. The aging treatment step may also be performed after the processing step described below.

[0095] [Cooling process] After the RTB permanent magnet is subjected to the aging treatment, the RTB permanent magnet is rapidly cooled in an Ar gas atmosphere (cooling step). This allows the above-mentioned RTB permanent magnet to be obtained. The cooling rate is not particularly limited, and may be 30°C / min or more.

[0096] [Processing process] The obtained RTB permanent magnet may be processed into a desired shape as necessary (processing step). Examples of processing methods include shaping such as cutting and grinding, and chamfering such as barrel polishing.

[0097] [Grain boundary diffusion process] A heavy rare earth element may be further diffused into the grain boundaries of the processed RTB permanent magnet (grain boundary diffusion step). There are no particular limitations on the method of grain boundary diffusion. For example, it may be carried out by attaching a compound containing a heavy rare earth element to the surface of the RTB permanent magnet by coating or vapor deposition, etc., and then carrying out a heat treatment. It may also be carried out by carrying out a heat treatment on the RTB permanent magnet in an atmosphere containing vapor of the heavy rare earth element. Grain boundary diffusion can further improve the HcJ of the RTB permanent magnet.

[0098] [Surface treatment process] The RTB permanent magnet obtained by the above steps may be subjected to surface treatment such as plating, resin coating, oxidation treatment, chemical conversion treatment, etc. (surface treatment step).

[0099] In this embodiment, the processing step, the grain boundary diffusion step, and the surface treatment step are performed, but these steps do not necessarily have to be performed.

[0100] The RTB permanent magnet obtained in the above manner has good magnetic properties and a wide sintering temperature range, which makes it possible to stably produce the RTB permanent magnet.

[0101] The RTB permanent magnets obtained in this manner are suitable for use as magnets in, for example, surface permanent magnet (SPM) rotating machines with a magnet attached to the rotor surface, interior permanent magnet (IPM) rotating machines such as inner rotor brushless motors, permanent magnet reluctance motors (PRMs), etc. Specifically, the RTB permanent magnets are suitable for use in spindle motors and voice coil motors for rotating hard disks in hard disk drives, motors for electric and hybrid cars, motors for electric power steering in automobiles, servo motors for machine tools, motors for vibrators in mobile phones, motors for printers, motors for generators, etc. EXAMPLES

[0102] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples.

[0103] (Preparation of alloys for RTB permanent magnets) Nd metal (purity 99% by mass or more), Nd-Pr alloy (didymium, purity 99% by mass or more), Tb metal (purity 99% by mass or more), ferroboron (Fe content 80% by mass, B content 20% by mass), Fe metal (purity 99% by mass or more), Co metal (purity 99% by mass or more), Zr metal (purity 99% by mass or more), Cu metal (purity 99% by mass or more), Al metal (purity 99% by mass or more), and Ga metal (purity 99% by mass or more) were weighed out to obtain the alloy composition shown in Table 1 below and mixed to obtain a raw material mixture. In Table 1, "T.RE" is the total content (mass%) of rare earth elements (Nd, Pr, Dy, and Tb), "T.RL" is the total content (mass%) of light rare earth elements (Nd and Pr). "bal." is the remainder. The Fe content is indicated as "bal." to indicate that the Fe content is the remainder when the entire RTB permanent magnet alloy, which contains elements other than the elements listed in Table 1, is taken as 100 mass %.

[0104] The obtained raw material mixture was loaded into an alumina crucible. The alumina crucible loaded with the raw material mixture was placed in a high-frequency vacuum induction furnace, and the atmosphere inside the high-frequency vacuum induction furnace was then replaced with Ar. The high-frequency vacuum induction furnace was then heated to melt the raw material mixture loaded into the alumina crucible, thereby obtaining a molten alloy. The obtained molten alloy was cast by a strip casting method using the casting device shown in Figure 12, to obtain a cast alloy ribbon (alloy for RTB-based permanent magnets). Casting was performed in an Ar atmosphere.

[0105] The temperature of the molten alloy, the roll surface roughness Rz of the chill roll, and the molten metal head pressure were appropriately selected so as to obtain the alloy for RTB rare permanent magnets shown in Table 2. Specifically, the temperature of the molten alloy (casting temperature) was selected within the range of 1300 to 1600°C, the roll surface roughness Rz of the chill roll was selected within the range of 5 to 50 μm, and the molten metal head pressure was selected within the range of 5 to 25 mm. The material of the chill roll was a copper alloy. The roll peripheral speed of the chill roll and the supply speed of the molten metal to the chill roll (supply speed per unit contact width between the molten metal and the chill roll) were adjusted to the values ​​shown in Table 2 below.

[0106] (Adjusting the electron microscope) A cross section of the obtained RTB permanent magnet alloy was observed with an electron microscope (manufactured by JEOL Ltd.) and the brightness and contrast of the electron microscope were adjusted in preparation for calculating the area ratio of the non-columnar crystal structure by brightness analysis.

[0107] First, the obtained RTB permanent magnet alloy was heat-treated at 1000°C for 120 minutes to obtain two heat-treated plates for incorporation into standard samples.

[0108] Next, a 0.1 mm thick Ni thin plate, a 0.1 mm thick Cu thin plate, and a 0.1 mm thick Zn thin plate were prepared. Next, the heat-treated plate, Ni thin plate, Cu thin plate, and Zn thin plate were embedded in an embedding resin for electron microscope observation. At this time, the heat-treated plate, Ni thin plate, Cu thin plate, Zn thin plate, and heat-treated plate were arranged in this order so that the cross sections of each plate were parallel to the thickness direction, to prepare a standard sample.

[0109] Next, the cross section of the standard sample was mirror-polished and gold was evaporated onto it.

[0110] Next, the standard sample was set in an electron microscope. The imaging mode was set to a backscattered electron image, with a magnification of 150 and a pixel count of 1280 × 960 pixels.

[0111] Next, the field of view was adjusted so that the Ni thin plate, the Cu thin plate, and the Zn thin plate were in that order within the same field of view.

[0112] Next, a pre-adjustment luminance histogram was created with 256 gradations, with the minimum luminance being 0 and the maximum luminance being 255, and the brightness was adjusted so that the position of the Cu luminance peak was approximately 150 (145-155). Furthermore, the contrast was adjusted so that the difference between the positions of the Ni luminance peak and the Cu luminance peak was approximately 55 (45-65), and the difference between the positions of the Cu luminance peak and the Zn luminance peak was approximately 45 (35-55). When adjusting the contrast, the brightness was additionally adjusted as necessary to maintain the position of the Cu luminance peak at approximately 150.

[0113] Next, while maintaining the contrast, the field of view was moved to a position where the heat-treated product was placed. Then, the magnification was increased so that the white phase (R-rich phase 13) was not included in the field of view and only the main phase 11 was included in the field of view. The maximum magnification was about 10,000 times. Furthermore, the brightness was adjusted so that the peak position of the brightness histogram was about 110 (105 to 115). Finally, the standard sample was collected from the electron microscope.

[0114] (Evaluation of RTB-based permanent magnet alloys) The microstructure of the RTB permanent magnet alloy was evaluated using an electron microscope with brightness and contrast adjusted by the above method.

[0115] First, samples for evaluation were taken. Specifically, in a process in which one production lot of RTB permanent magnet alloys was supplied by the above-mentioned strip casting method, alloy flakes were sampled from the RTB permanent magnet alloys supplied at regular time intervals. Thirty alloy flakes were randomly taken from the RTB permanent magnet alloys, and each alloy flake was used as an evaluation sample.

[0116] Next, the thickness of the collected evaluation sample was measured.

[0117] Of the 30 evaluation samples, the second, third, and fourth thickest samples were selected as thick samples, the 14th, 15th, and 16th thickest samples were selected as near-average samples, and the 27th, 28th, and 29th thickest samples were selected as thin samples.

[0118] Next, the nine selected evaluation samples were attached with instant adhesive and processed so that a cross section parallel to the thickness direction could be observed. When attaching the evaluation samples, they were arranged so that it was clear which evaluation sample was a thick sample, which was a sample near the average, or which was a thin sample.

[0119] Next, the nine evaluation samples attached with instant adhesive were embedded in resin together to form one embedded resin sample. The cross section parallel to the thickness direction was then mirror-finished to prepare an observation surface.

[0120] Next, the imaging mode was a backscattered electron image, the magnification was 350 times, and the number of pixels was 1280 × 960 pixels, and the observation range was set. The observation range was selected from the observation surface of each evaluation sample in an average state. Next, the area ratio of the non-columnar crystal structure in the observation range was calculated by analysis.

[0121] The specific analysis procedure is explained below. First, the above observation range was divided into sections at regular intervals. Each section had a dimension of 50 pixels.

[0122] Next, a luminance histogram was created for each section, and the peak position and σ of the luminance histogram were obtained for each section.

[0123] Next, each section was judged as to whether it was a non-columnar crystal structure. Specifically, a section in which the peak position of the brightness histogram was 130 or more and 200 or less, and σ was 20 or more and 40 or less, was deemed to be a non-columnar crystal structure. A section in which the peak position of the brightness histogram or σ was outside the above range was deemed not to be a non-columnar crystal structure. Each section in the observation range was judged as to whether it was a non-columnar crystal structure, and the number of sections in the observation range that were non-columnar crystal structures was divided by the number of all sections to determine the area ratio of the non-columnar crystal structure in the cross section of each evaluation sample.

[0124] The area ratio of the non-columnar crystal structure in the cross section of each evaluation sample was then averaged to calculate the area ratio of the non-columnar crystal structure in the cross section of one production lot of the RTB permanent magnet alloy. The results are shown in Table 2.

[0125] (Production of RTB permanent magnets) After hydrogen was absorbed into the RTB permanent magnet alloy at room temperature, hydrogen was removed in a vacuum at 600°C for 1 hour (coarse pulverization) to obtain an alloy powder (coarse pulverized powder). In this example, each step from the hydrogen pulverization to sintering (fine pulverization and molding) was carried out in an Ar atmosphere with an oxygen concentration of less than 50 ppm or in a vacuum.

[0126] Next, zinc stearate and stearic acid amide were added to the alloy powder as grinding aids and mixed using a Nauta mixer. The amount of zinc stearate added was 0.05 parts by mass per 100 parts by mass of the coarsely ground powder. The amount of stearic acid amide added was 0.05 parts by mass per 100 parts by mass of the coarsely ground powder. Then, fine grinding was performed using a jet mill to obtain a finely ground powder with an average particle size of about 3.0 μm.

[0127] The resulting finely pulverized powder was filled into a die placed in an electromagnet, and compacted in a magnetic field by applying a pressure of 120 MPa while applying a magnetic field of 1200 kA / m to the die, to obtain a compact.

[0128] The obtained green body was then sintered by holding it in a vacuum at 1,050°C for 4 hours and then rapidly cooled to obtain a sintered body having the magnet composition shown in Table 1. The obtained sintered body was then subjected to a two-stage aging treatment at 900°C for 1 hour and at 500°C for 1 hour (both in an Ar atmosphere) to obtain an RTB-based permanent magnet (RTB-based sintered magnet).

[0129] [Magnetic properties] The Br, HcJ and Hk / HcJ of each sample were measured using a BH tracer. Br was measured at room temperature for all samples. HcJ and Hk / HcJ were measured at room temperature for samples 1 to 5. HcJ and Hk / HcJ were measured at 150°C for the other samples. In this example, Hk is the value of the magnetic field when the magnetization is Br x 0.9 in the second quadrant of the demagnetization curve.

[0130] [Table 1]

[0131] [Table 2]

[0132] Among samples 1 to 5, the RTB permanent magnets of sample numbers 1 to 4, which were produced using alloys for RTB permanent magnets in which the area ratio of the non-columnar crystal structure, i.e., the area ratio of the sections in which the peak position is 130 to 200 and σ is 20 to 40, is 1.0% or more and 30.0% or less, had higher Br, similar HcJ, and higher Hk / HcJ than the RTB permanent magnet of sample number 5, which was produced using an alloy for RTB permanent magnets produced under the same conditions except that the area ratio of the non-columnar crystal structure was outside the above range. In particular, the Hk / HcJ at room temperature was higher.

[0133] The RTB permanent magnets of sample numbers 7 to 12, which were made using alloys for RTB permanent magnets in which the area ratio of the non-columnar crystal structure was 4.0% or more and 30.0% or less, had higher HcJ than sample number 6, which was made under the same conditions except that the area ratio of the non-columnar crystal structure was 1.0% or more and less than 4.0%.

[0134] For samples 7 to 12, the RTB permanent magnets produced under the same conditions except that the area ratio of the non-columnar crystal structure in the RTB permanent magnet alloy was changed from 4.0% to 30.0% showed a tendency for the HcJ to increase as the area ratio of the non-columnar crystal structure in the RTB permanent magnet alloy increased.

[0135] Sample No. 13 had a B content of 0.96 mass%, which was higher than the other samples. Therefore, even under casting conditions similar to those of the other samples, the area ratio of the non-columnar crystal structure was reduced. As a result, HcJ was reduced compared to the other samples.

[0136] It was also confirmed that in all samples in which the area ratio of the non-columnar crystal structure was 1.0% or more and 30.0% or less, the area ratio of structures other than the chilled crystal structure in the non-columnar crystal structure was 85% or more and 95% or less. [Explanation of symbols]

[0137] 1...Chill crystal structure 3...Microscopic dotted R-rich phase-containing structure 4…Punctate R-rich phase-containing structure 5...Micro-linear R-rich phase-containing structure 6...Large dot-like R-rich phase-containing structure 7…Normal organization 11…Main phase 13…R-rich phase 21...Cooling roll 23…Tundish 25…Molten alloy 27…Molten metal head pressure

Claims

1. obtaining an image of a cross-section of the material; Dividing the obtained image into a number of sections; measuring the luminance of a plurality of pixels included in each partition; obtaining a luminance histogram for each section from the luminance of each pixel; Identifying the type of microstructure of each section from the peak position and peak standard deviation in the brightness histogram of each section; Calculating the total area percentage of the sections having the specific microstructure, A method for evaluating a material, in which a luminance histogram is created in 256 gradations, with the minimum luminance being 0 and the maximum luminance being 255, and the total area ratio of sections in which the peak position is 130 to 200 and the peak standard deviation is 20 to 40 is calculated.

2. The method for evaluating a material according to claim 1 , wherein the material is an alloy.

3. 3. The material evaluation method according to claim 2, wherein the alloy is an R-T-B type alloy for permanent magnets, R being a rare earth element, T being a transition metal element, and B being boron.

4. embedding two or more image preparation plates in a substrate to contain them within the same field of view of an electron microscope; creating an unadjusted luminance histogram for the field of view; adjusting the positions of the luminance peaks originating from each thin plate in the unadjusted luminance histogram to a predetermined position and adjusting the difference between the positions of the luminance peaks originating from each thin plate to a predetermined size; The method for evaluating a material according to any one of claims 1 to 3, wherein an image of a cross section of the material is obtained using an electron microscope adjusted using a method for adjusting an electron microscope comprising the steps of:

Citation Information

Patent Citations

  • Method of evaluating metal structure of r-t-b magnet alloy

    JP2008058323A

  • Substrate inspection device and substrate inspection method using charged particle beam

    JP2008252085A

  • Microscopic image analysis method of sintered ore

    JP2014137344A

  • Pattern measurement program, pattern measurement method, and device

    JP2017102039A

  • Image processing device for realizing material informatics

    JP2019027938A